ANALISIS METODE DEDUKSI DALAM MEMAHAMI MASALAH YANG TERJADI DI GEREJA TORAJA JEMAAT RANTEPASANG - Ayu Purnama Sari; Ela Olyviea Tandi; Meli Kuse; Oktavani Lukin Caliane; Resti Kinda (STT Kingdom, 2023)
The purpose of this research is to analyze the deduction method in understanding the problems that occur in the Toraja Church of the Rante Pasang congregation. The problems that occurred in the Rantetangan congregation affected the life of the church, especially in terms of spirituality. one of the problems that exist in the Toraja Church of the Rante Pasang congregation is the habit of playing gambling. This custom is not only carried out by church members but also by church elders. The habit of playing gambling by the elders has a bad influence on the spiritual development of the congregation. by using the method of deductive reasoning, a study can reach conclusions that are based on theories that have been proven true.